Role of Sexual Intercourse after Shockwave Lithotripsy for Distal Ureteral Stones: A Randomized Controlled Trial - Li, Wenfeng; Mao, Yuansheng; Lu, Chao; Gu, Yufei; Gu, Xin; Hua, Bao; Pan, Weixin (Urology Journal, 2020)
Purpose: To explore whether sexual intercourse is beneficial to the clinical outcome of SWL for ureteral calculi of 7-15 mm in the distal ureter. Materials and Methods: Between March 2016 and January 2017, 225 patents with a stone (7-15 mm) in distal ureter were randomly divided into three groups after SWL: Group 1 was asked to have sexual intercourse at least three times a week, Group 2 was administered tamsulosin 0.4 mg/d and Group 3 was received standard therapy alone and served as the controls. Stone free rate, time to stone expulsion, pain score at admission, number of hospital visits for pain and steinstrasse were recorded in 2 weeks. Results: 70 patients in Group 1, 71 patients in Group 2 and 68 patients in Group 3 were enrolled to the study. At the end of the first week and the second week, the stone free rates for Group 1 (68.6%, 80.0%) and Group 2 (69.0%, 81.7%) were approximately the same, but were significantly higher than Group 3 (50.0%, 63.2%) (P = .031, P = .022). The VAS scores of Groups 1 and 2 were slightly higher than those of Group 3 (P = .233). The number of patients in Group 3 who visited the emergency room for pain was significantly higher than in the other two groups (P = .015). At the end of the second week, the incidence of steinstrasse in Groups 1 and 2 was significantly lower (2.9%, 2.8% vs 11.8%) (P = .034). Conclusion: At least three sexual intercourses per week after SWL can effectively improve the stone free rate, reduce the formation of steinstrasse and relieve renal colic. It provides a choice for urologists in the SWL treatment of lower ureteral calculi.